RESEPSI HADIS DALAM TRADISI SYAWALAN DI MASYARAKAT JAWA TENGAH - Susanti, Rini (Al-Bayan: Journal of Hadith Studies, 2023)
A religious tradition in society does not occur suddenly. The tradition is formed as a result of the process of transmission and transformation of understanding of religious texts, both from the verses of the Qur'an and the sayings of the Prophet. The role of local leaders in transmitting the interpretation of these texts is crucial. The reception of understanding from these local leaders is then followed by the surrounding community, thus becoming an inherited tradition. One of these inherited traditions is found in the Central Java community, specifically in the city of Pekalongan. The people of Pekalongan have a unique tradition called "Syawalan". They regularly make giant-sized "lopis" (a traditional Javanese snack made from glutinous rice) every 8th of Syawal. This paper will discuss the reception of hadith in the Syawalan tradition in Pekalongan and the meaning of that tradition. The method used in this research is qualitative-phenomenological. The results of this research are as follows: Firstly, the reception of hadith related to fasting six days in the month of Syawal and the hadith emphasizing the honor of guests are expressed by the people of Pekalongan through the tradition of making giant lopis during Syawalan. Secondly, the Syawalan tradition itself has several meanings, including philosophical, spiritual, social, and psychological meanings